2018
DOI: 10.1007/s11356-018-2106-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth, physiological responses, and copper accumulation in seven willow species exposed to Cu—a hydroponic experiment

Abstract: Selecting plant species, especially woody species, that can tolerate and accumulate high levels of heavy metals is crucial for the purpose of phytoremediation. In the present study, seven willow species/clones were evaluated for their variations in copper (Cu) tolerance, Cu accumulation, and their relative physiological responses, when exposed to different doses of Cu (control, 15, and 120 μM) in a hydroponic system for 40 days. Upon Cu exposure, all tested willow species/clones (Salix, S.) remained relative n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 53 publications
2
17
0
1
Order By: Relevance
“…In this work, strains of these two genera were capable of simultaneous Cr(VI) removal and pyrene degradation. Roots and shoots are important plant organs that can be negatively affected by contacting with heavy metals, such as Cr, cadmium and copper 7,21,22 . Zong et al 7 showed that there were positive correlations between total Cr in peanuts and total root length, root surface area, and root volume, and that Cr(VI) at concentrations ranging from 75 to 100 µmol/L significantly decreased the root and shoot biomass of peanut.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, strains of these two genera were capable of simultaneous Cr(VI) removal and pyrene degradation. Roots and shoots are important plant organs that can be negatively affected by contacting with heavy metals, such as Cr, cadmium and copper 7,21,22 . Zong et al 7 showed that there were positive correlations between total Cr in peanuts and total root length, root surface area, and root volume, and that Cr(VI) at concentrations ranging from 75 to 100 µmol/L significantly decreased the root and shoot biomass of peanut.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, heavy metals of excessive dose can damage photosynthesis in terms of chlorophyll degradation []. Cao et al [22], also reported that excessive Cu (120 μM as CuSO 4 ) can severely reduce chlorophyll pigments, resulting in lower Gs and Pn. As a micronutrient, Cu at lower critical concentration is required to improve the plant development [24].…”
Section: Copper Accumulation In Lettucementioning
confidence: 99%
“…Wang et al (2019) Reported that the application CuO-NPs mixed with the soil were no significant change in Chl a content, intercellular CO 2 concentration or photosynthetic rate in leaves of lettuce while Cu-NPs @ 200 mg/kg were found Chl b in the lettuce leaves is decreased as compared with control. Cao et al (2018) revealed that the chlorophyll pigments were severely reduced by the excessive Cu (120 μM as CuSO 4 ) resulting the lower stomatal conductance and photosynthetic rate.…”
Section: Satdev and Mandalmentioning
confidence: 99%